2020
DOI: 10.1016/j.gore.2020.100639
|View full text |Cite
|
Sign up to set email alerts
|

Primary B-Cell lymphoma of the uterine cervix presenting with right ureter hydronephrosis: A case report

Abstract: Highlights Primary cervical B-cell lymphoma can mimic locally advanced cervical cancer. Primary cervical lymphoma should be suspected in women with normal Pap smear and rapidly growing tumor. Initial biopsies of primary gynecological lymphomas can be non-contributory. Treatment should include R-CHOP based chemotherapy with methotrexate for neuromeningeal prophylaxis. Fertility-sparing management should be offered to yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Thus, routine cervical cytology smears or superficial tissue biopsy results may be prone to generating false negatives or missing the lesion in deeper sites. ( Del et al, 2020 , Chan et al, 2005 ) In this case, cervical cytology revealed atypical squamous cells of undetermined significance (ASCUS), while HPV and SCC tests were negative, suggesting abnormal lesions in the cervix. Due to the obvious lesion, biopsy samples were taken during gynecological examination.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, routine cervical cytology smears or superficial tissue biopsy results may be prone to generating false negatives or missing the lesion in deeper sites. ( Del et al, 2020 , Chan et al, 2005 ) In this case, cervical cytology revealed atypical squamous cells of undetermined significance (ASCUS), while HPV and SCC tests were negative, suggesting abnormal lesions in the cervix. Due to the obvious lesion, biopsy samples were taken during gynecological examination.…”
Section: Discussionmentioning
confidence: 75%
“…Within both veterinary and human literature, the author was unable to find any reports of a separate neoplastic organ invading the tissues of the ureter, though some papers alluded to the possibility in humans 14 . In most cases where hydronephrosis was found secondary to a separate abdominal mass, it was due to compression of the ureter by the mass itself or associated fibrotic tissue 15–18 . Obstruction secondary to infiltrative disease was decided in this case with the appearance of the mass entering the ureter and extending distally into the UVJ where it was then visualized within the bladder.…”
Section: Discussionmentioning
confidence: 94%
“…14 In most cases where hydronephrosis was found secondary to a separate abdominal mass, it was due to compression of the ureter by the mass itself or associated fibrotic tissue. [15][16][17][18] Obstruction secondary to infiltrative disease was decided in this case with the appearance of the mass entering the ureter and extending distally into the UVJ where it was then visualized within the bladder. Had the UVJ not been affected, compression from adjacent lymphadenopathy could not have been definitively ruled out without advanced imaging and/or necropsy.…”
Section: Discussionmentioning
confidence: 99%
“…Primary lymphomas of the female genital tract are extremely rare, representing 0.2-1.1% of extranodal NHL and less than 0.5% of total gynecological malignancies 5 .…”
Section: Discussionmentioning
confidence: 99%